Cytotoxic potential of camel whey and milk on cervix cancer (HeLa) cell line (Asian Journal of Medical and Biological Research, 2019)
Camel milk is an important nutritional source that historically been used in the treatment of cancer. Therefore, the main aim of the present study is to determine the in vitro anticancer effect of both camel milk and whey against cervix cancer (HeLa) cells. To perform that, skimmed milk as well as whey immunoglobulins concentrate samples were prepared at different concentrations (0, 1, 2.5, 5, 7.5 and 10 mg/ml). Then, the in vitro effect of the prepared concentrations on HeLa cells morphology and growth was investigated by tissue culture technique. Moreover, the anticancer activity of camel milk and whey against HeLa cells was estimated by the 3-[4, 5-dimethylthiazole-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. The obtained results displayed that both camel milk and whey reduced the viability of HeLa cells specially at 7.5 and 10 mg/ml. In addition, the viability of treated HeLa cells reduced after addition of both camel milk and whey to approximately 15% in a concentration dependent manner. In conclusion, this study showed the in vitro cytotoxic effect of camel milk and whey as they inhibited the growth of HeLa cells.Asian J. Med. Biol. Res. June 2019, 5(3): 231-236